A comprehensive analysis of nanoscale single- and multi-gate MOSFETs. (June 2016) - Sharma, Rupendra Kumar; Dimitriadis, Charalabos A.; Bucher, Matthias
Abstract: Analog/RF performance of nanoscale triple gate FinFETs and planar single-gate (SG) and double-gate (DG) SOI MOSFETs is examined via extensive 3D device simulations. Well-designed DG MOSFETs attain higher values of cut-off frequency for both lower and higher drain currents, whereas triple-gate (TG) FinFETs offer higher intrinsic gain while compromising cut-off frequency. For longer channel lengths, SG MOSFETs show slightly higher cut-off frequency in comparison to multi-gate (MG) MOSFETs, whereas MG MOSFETs exhibit higher cut-off frequency for lower channel lengths. A unique figure of merit, gain transconductance frequency product (GTFP) for best trade-off among gain, transconductance, and speed is compared. Double-gate MOSFETs exhibit higher GTFP over a wide range of device scaling, thus remain a good candidate for analog/RF applications. Furthermore, the RF linearity performance of these devices has been examined.